The Impact of Financial Technology on Financial Performance in General Banks in Indonesia - Riska Andani; Busra Busra; Yusri Hazmi (Electronic Journal of Education, Social Economics and Technology, 2026)
The rapid development of Financial Technology (Fintech) has significantly reshaped banking operations in Indonesia. This study investigates the impact of Fintech represented by Phone Banking, Mobile Banking, and Internet Banking on the financial performance of Indonesian commercial banks measured by Return on Assets (ROA). Using quarterly data from 2022 to 2024 and applying the Vector Error Correction Model (VECM), the research confirms a long-term equilibrium among the variables. Long-term estimation results reveal that only Phone Banking significantly affects ROA, while Mobile Banking and Internet Banking do not. In the short term, Mobile Banking influences Phone Banking, and both Phone and Internet Banking exhibit Granger causality toward ROA, though without direct short-term significance. The findings suggest that while digital banking services are broadly utilized, their impact on profitability remains limited, potentially due to high operational costs and shifting customer preferences. The study recommends that banks refine digital strategies, particularly in Phone Banking, to enhance their financial performance. The research also demonstrates the utility of VECM in analyzing both short-term dynamics and long-term relationships in digital finance.